HIV and schistosomiasis in rural Zimbabwe: the association of Retinol-binding protein with disease progression, inflammation and mortality. (April 2015) - Kotzé, Sebastian Ranzi; Zinyama-Gutsire, Rutendo; Kallestrup, Per; Benn, Christine Stabell; Gomo, Exnevia; Gerstoft, Jan; van Dam, Govert; Mortensen, Ole Hartvig; Ullum, Henrik; Erikstrup, Christian
Highlights: RBP is a marker of vitamin-A status and a negative acute-phase protein. This is the largest study of interactions between schistosomiasis and HIV. RBP was negatively correlated with markers of HIV progression and inflammation. RBP was lower in those co-infected with HIV and S. mansoni . RBP was negatively correlated with schistosomiasis intensity in these individuals. Summary: Background: Vitamin A has widespread effects on immune function and is therefore interesting in HIV-infection. Retinol-binding protein (RBP or RBP4) is a negative acute-phase protein and a marker of vitamin A status. Our aim was to investigate the association of RBP with HIV progression, infection with schistosomiasis, inflammatory cytokines, and mortality. Methods: The study included 192 HIV-infected and 177 HIV-uninfected individuals from Mupfure in rural Zimbabwe. Of these, 208 were infected with Schistosoma haematobium, 27 with S. mansoni and 48 with both. Plasma RBP, HIV-RNA, CD4 cell count, haemoglobin, cytokines, clinical staging (CDC category), self-reported level of function (Karnoffsky Performance Score, KPS) and schistosomiasis status were assessed at baseline. Participants were followed up for survival 3-4 years post-enrolment. Results: RBP levels were lower in HIV-infected individuals(p<0.0001). Among HIV-infected individuals, multivariable analysis showed RBP to be positively correlated with CD4 cell count(p=0.050), KPS(p=0.003), and haemoglobin(p<0.0001) and negatively correlated with HIV-RNA(p<0.0001), CDC category(p<0.0001), tumor necrosis factor-receptor II(p<0.0001) and interleukin(IL)-6(p=0.004), as well as with IL-8(p=0.005) and IL-10(p=0.003) for HIV-infected men. Furthermore, among HIV-infected individuals RBP correlated negatively with schistosomiasis(p=0.038) and intensity of infection: circulating anodic antigen(p=0.014), circulating cathodic antigen(p<0.0001) and faecal egg output(p=0.004). Conclusions: In HIV-infected individuals, RBP was negatively associated with levels of inflammatory markers, markers of HIV progression, infection with schistosomiasis and markers of schistosomal intensity.